Field Monitoring and Numerical Analysis of the Reinforced Concrete Foundation of a Large-Scale Wind Turbine. (5th July 2021) - Zhou, Yanming; Liu, Xinxi; Deng, Zongwei; Gao, Qian-Feng
Abstract : The objective of this study is to examine the performance of the shallow reinforced concrete foundation of a large-scale wind turbine under the influence of environmental loads. A 2 MW horizontal-axis onshore wind turbine supported by a shallow concrete foundation was considered. The foundation stresses, foundation settlements, and static and dynamic contact pressures at various positions of the shallow foundation were monitored from the construction phase to the operation phase in the field. Numerical simulations were also performed to further analyze the behavior of the wind turbine foundation in different cases. The results demonstrate that the responses of the reinforced concrete foundation, i.e., foundation stresses, contact pressures, and foundation settlements, were variables closely related to the wind direction and wind speed. The distribution of foundation stresses suggested that a reasonable design of steel reinforcement cages around the foundation steel ring is important. The dynamic contact pressure of the foundation could reach 5 kPa, so the influence of dynamic wind loads on the foundation response could not be always neglected, particularly for the foundations seated on weak soils. The foundation settlement during the operation phase could be characterized by the logistic model, but its distribution was uneven due to the presence of eccentric upper weight and wind load. The findings would provide guidance for the foundation design of onshore wind turbines in hilly areas.